Practical and customizable study strategies for clerkship year success - Johnston, Hannah; Zhao, Caroline; Hu, Yenya (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
The transition from a pre-clerkship curriculum to the clerkship year presents a need to re-examine and modify study strategies for clinical subject examinations and ultimately the United States Medical License Examination STEP 2 Clinical Knowledge. Efficient and effective learning are keys in balancing the significantly increased responsibility of patient care and decreased time for examination preparation.We describe several customizable study approaches, advice on selecting resources, and methods for applying the educational framework of deliberate practice and corrective feedback to learning during a medical student’s clerkship years. These strategies focus on intentional and outcome-driven self-assessments to identify and patch knowledge gaps tailored to the clerkship year that will empower learners.